Anti-Nematodal Efficacy of Ivermectin (Oral) and Extracts of Coriandrum sativum in Sheep in Barani Livestock Production Research Institute (BLPRI) Kherimurat, District Attak Punjab Pakistan - Memrez Khushal Gigyani; Khurshaid Anwar; Muhammad Ovais Omer; Habibun Nabi; Insanud Din; Anwarud Din; Zill E. Huma (Journal of Basic & Applied Sciences, 2018)
Anthelmentic resistance (AR) is one of the major problems of livestock industry in developing countries. Using indigenous medicinal plants may be an alternate way to overcome this problem. Total 60 sheep nematode positive were selected and divided into 6 groups having 10 sheep each. Group A as un-treated control, group B was given Ivermectin at the dose rate of 0.2mg/kg body weight Group C and Group D was given the Chloroformic extract while Group E and F was given the Methalonic extract of Coriandrum sativum whole plant at the dose rate of 50 mg/kg and 100 mg/kg body weight respectively. After treatments, fecal eggs count reduction test (FECRT) (eggs/g) was carried out on day 7, 14 and 28. The EPG in untreated group at day 28 was increased 21.6%. Significant decrease in EPG was only observed at day 28 in Ivermectin treated group (92.6%) and Methanolic extract at a dose rate of 100 mg/kg body weight (60.69%). No significant results were recorded in remaining groups. It was concluded that 100 mg/kg body weight Methalonic extract of Coriandrum sativum would be a best alternative as anti-nematodal drug.